2012
DOI: 10.1097/brs.0b013e318267f7f5
|View full text |Cite
|
Sign up to set email alerts
|

Crosscultural Adaptation, Reliability, and Validity of the Japanese Version of the Neck Disability Index

Abstract: The NDI-J is a valid, reliable, and responsive tool that can be used to assess neck pain in Japanese outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 25 publications
6
19
0
Order By: Relevance
“…The variations in the correlations between single items and total scores (0.34 to 0.89) in the present study were comparable to the results of other studies (0.40 to 0.84) [10, 25, 35]. The present study found excellent test-retest reliability, comparable to the original study and other translations [10–12, 14, 17, 19, 2123, 28, 29, 35, 60]. However, the test-retest reliability is higher compared to the German (0.81), Dutch (0.84), Italian (0.84) and Thai (0.85) versions of the NDI [26, 27, 64, 65].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The variations in the correlations between single items and total scores (0.34 to 0.89) in the present study were comparable to the results of other studies (0.40 to 0.84) [10, 25, 35]. The present study found excellent test-retest reliability, comparable to the original study and other translations [10–12, 14, 17, 19, 2123, 28, 29, 35, 60]. However, the test-retest reliability is higher compared to the German (0.81), Dutch (0.84), Italian (0.84) and Thai (0.85) versions of the NDI [26, 27, 64, 65].…”
Section: Discussionsupporting
confidence: 90%
“…An excellent internal consistency was demonstrated by a Cronbach’s alpha value of 0.90, which is well in the range of the findings of earlier studies (0.74–0.96) [10, 12, 14, 19, 2123, 25, 28, 29, 35, 60, 64]. The variations in the correlations between single items and total scores (0.34 to 0.89) in the present study were comparable to the results of other studies (0.40 to 0.84) [10, 25, 35].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It was used to test the convergent validity of the PSFS in this study. The psychometric properties of the Japanese version of the NDI have been well documented [8].…”
Section: Neck Disability Indexmentioning
confidence: 99%